Preemptive intrathecal administration of endomorphins relieves inflammatory pain in male mice via inhibition of p38 MAPK signaling and regulation of inflammatory cytokines - Ting Zhang; Nan Zhang; Run Zhang; Weidong Zhao; Yong Chen; Zilong Wang; Biao Xu; Mengna Zhang; Xuerui Shi; Qinqin Zhang; Yuanyuan Guo; Jian Xiao; et al. (Journal of Neuroinflammation, 2018)
Abstract Background Preemptive administration of analgesic drugs reduces perceived pain and prolongs duration of antinociceptive action. Whereas several lines of evidence suggest that endomorphins, the endogenous mu-opioid agonists, attenuate acute and chronic pain at the spinal level, their preemptive analgesic effects remain to be determined. In this study, we evaluated the anti-allodynic activities of endomorphins and explored their mechanisms of action after preemptive administration in a mouse model of inflammatory pain. Methods The anti-allodynic activities of preemptive intrathecal administration of endomorphin-1 and endomorphin-2 were investigated in complete Freund’s adjuvant (CFA)-induced inflammatory pain model and paw incision-induced postoperative pain model. The modulating effects of endomorphins on the expression of p38 mitogen-activated protein kinase (p38 MAPK) and inflammatory mediators in dorsal root ganglion (DRG) of CFA-treated mice were assayed by real-time reverse transcription-polymerase chain reaction (RT-PCR), Western blotting, or immunofluorescence staining. Results Preemptive intrathecal injection of endomorphins dose-dependently attenuated CFA-induced mechanical allodynia via the mu-opioid receptor and significantly reversed paw incision-induced allodynia. In addition, CFA-caused increase of phosphorylated p38 MAPK in DRG was dramatically reduced by preemptive administration of endomorphins. Repeated intrathecal application of the specific p38 MAPK inhibitor SB203580 reduced CFA-induced mechanical allodynia as well. Further RT-PCR assay showed that endomorphins regulated the mRNA expression of inflammatory cytokines in DRGs induced by peripheral inflammation. Conclusions Our findings reveal a novel mechanism by which preemptive treatment of endomorphins attenuates inflammatory pain through regulating the production of inflammatory cytokines in DRG neurons via inhibition of p38 MAPK phosphorylation.